Apparent beam size definition of focused ion beams based on scanning electron microscopy images of nanodots - Vladov, Nikola; Segal, Joel; Ratchev, Svetan (AIP, 2015)
In this paper the new term apparent beam size of Focused Ion Beam (FIB) is introduced and an original method of its evaluation is demonstrated. Traditional methods of measuring the beam size, like the knife edge method, provide information about the quality of the beam itself but practically they do not give information on the FIB sputtering resolution. To do this, it is necessary to take into account the material dependant interaction of the beam with the specimen and the gas precursor in the vacuum chamber. The apparent beam size can be regarded as the smallest possible dot that FIB can sputter in a given specimen. The method of evaluating it, developed in this paper, is based on the analysis of a series of scanning electron images of FIB produced nanodots. Results show that the apparent beam size can be up to 5 times larger than the actual physical size of the beam and it is significantly influenced by the presence of gas precursor. It is also demonstrated that the apparent beam size can be used as a reference value for optimisation of the beam step during raster scanning.